The Role of Breastfeeding Fathers in Patriarchal Culture in East Sumba Regency East Nusa Tenggara Province - Ngundju Awang, Mariana; Maria Kristin, Diyan; A A Woda , Wilhelmina (Green Publisher Indonesia, 2023)
One of the failure factors in exclusive breastfeeding is the role of the husband who has a higher position than women. The purpose of this study was to determine